A multicenter pilot study of the effectiveness and safety of a monopolar radiofrequency device for improving periorbital and facial fine wrinkles - Hee Joo Yang; Sun Young Choi; Joon Min Jung; Yoon-Seo Jo; Hye Sung Han; Young In Lee; Ju Hee Lee; Chong Hyun Won (Journal of Dermatological Treatment)
Purpose This study aimed to investigate the effectiveness and safety of a new monopolar radiofrequency device equipped with a 5 cm2 tip, against fine wrinkles around the eyes and cheeks.Materials and methods This multicentered, prospective pilot study involved treating participants with mild-to-moderate wrinkles on both periorbital areas and cheeks using the monopolar radiofrequency device for one session. One and four months after treatment, wrinkle reduction, overall esthetic improvement, adverse events, and vital signs were evaluated.Results The study involved 13 participants (age: 35–62 years) and on a five-point scale, periorbital wrinkles showed a significant reduction at 4 weeks (0.96 ± 0.65) and 16 weeks (1.04 ± 0.59). On a five-point scale, cheek wrinkles also decreased at weeks 4 and 16 (1.00 ± 0.55 and 1.12 ± 0.64, respectively). On a five-point scale (range: −1–3), overall global esthetic improvement was rated by the participants at weeks 4 and 16 to be 2.23 ± 0.80 and 2.31 ± 0.61, respectively. Adverse events were not observed during the follow-up.Conclusion A single session using the new monopolar radiofrequency device equipped with a 5 cm2 tip safely and effectively improves mild-to-moderate periorbital and facial wrinkles.